Multimodal endovascular management of acute ischemic stroke in patients over 75 years old is safe and effective. (11th July 2012) - Ghobrial, George M; Chalouhi, Nohra; Rivers, Lana; Witte, Samantha; Davanzo, Justin; Dalyai, Richard; Gardecki, Michelle L; Jabbour, Pascal; Gonzalez, Fernando; Dumont, Aaron S; Rosenwasser, Robert H; Tjoumakaris, Stavropoula
Abstract : Introduction: Greater attention has been directed to endovascular recanalization of acute ischemic stroke in septuagenarians and above. Technique: A retrospective chart review was conducted to include patients treated for acute ischemic stroke from 2006 to 2012. All patients underwent initial neurological assessment and non-contrast head CT. Patients treated from 2009 to 2012 additionally received emergent CT angiogram and CT perfusion. 51 patients met the clinical and radiographic criteria and underwent multimodal endovascular revascularization for acute ischemic events. Results: All patients underwent cerebral angiography and met angiographic criteria for endovascular thrombolysis. 34 patients (67%) were older than 80 years of age. 23 patients (45%) received intravenous tissue plasminogen activator prior to admission. Eight (16%) patients underwent stent placement after intra-arterial thrombolysis, 10 (20%) underwent balloon angioplasty and seven (14%) underwent both angioplasty and stent placement. 21 (41%) required only intra-arterial thrombolytics. An improvement in Thrombolysis in Myocardial Infarction score was noted in 34 patients (67%). The average modified Rankin Scale score on discharge was 3.9. Symptomatic intracranial hemorrhage occurred in three patients (6%); none required surgery. One patient (1.9%) had a postoperative retroperitoneal hematoma, which was managed conservatively. Two fatalities resulted from intraoperative vessel rupture (3.9%), with a combined morbidity and mortality of 27.5%. Conclusions: Multimodal endovascular recanalization of acute ischemic stroke is a relatively safe treatment option in patients older than 75 years of age. Careful patient selection by clinical and radiographic inclusion criteria is necessary for the successful management of stroke in this age group.